2014
DOI: 10.1159/000365331
|View full text |Cite
|
Sign up to set email alerts
|

Anopheles gambiae Blood Feeding Initiates an Anticipatory Defense Response to Plasmodium berghei

Abstract: Mosquitoes have potent innate defense mechanisms that protect them from infection by diverse pathogens. Much remains unknown about how different pathogens are sensed and specific responses triggered. Leucine-Rich repeat IMmune proteins (LRIMs) are a mosquito-specific family of putative innate receptors. Although some LRIMs have been implicated in mosquito immune responses, the function of most family members is largely unknown. We screened Anopheles gambiae LRIMs by RNAi for effects on mosquito infection by ro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
54
2

Year Published

2015
2015
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 45 publications
(60 citation statements)
references
References 71 publications
4
54
2
Order By: Relevance
“…gallinaceum infection. It is possible that levels of H 2 O 2 , nos or the immune genes that we examined could have been changed in response to blood feeding or severity of Plasmodium infection, as both factors are linked to oxidative stress response [56, 66, 83, 84]. Additionally, there could have been systemic change in the mosquito oxidative stress and immune responses as a result of these processes, and this may have contributed to the response of Wolbachia to pathogens, even under conditions of starvation.…”
Section: Discussionmentioning
confidence: 99%
“…gallinaceum infection. It is possible that levels of H 2 O 2 , nos or the immune genes that we examined could have been changed in response to blood feeding or severity of Plasmodium infection, as both factors are linked to oxidative stress response [56, 66, 83, 84]. Additionally, there could have been systemic change in the mosquito oxidative stress and immune responses as a result of these processes, and this may have contributed to the response of Wolbachia to pathogens, even under conditions of starvation.…”
Section: Discussionmentioning
confidence: 99%
“…Their rapidly diverging sequences and previous work showing that some of these are under strong positive selection (Arcà et al 2014) lends support to the notion that host immune pressures are a dominant driving force acting on salivary gland genes essential for blood feeding. At the same time, the presence of saglin (SG1f:AGAP000610) that acts as a binding partner for parasitic TRAP protein (Ghosh et al 2009;Upton et al 2015) but also five more members of this SG1 family may indicate the impact of pathogen-driven pressures (Fig. 5B).…”
Section: Rapidly Evolving Sex-biased Genes Are Confined To a Few Biolmentioning
confidence: 99%
“…5B). Among these are a cluster on Chromosome 2L containing an array of leucine-rich repeat immune proteins (LRIM 8A:AGAP007454, 8B:AGAP007456, 9:AGAP007453, and 10:AGAP007455) (Waterhouse et al 2010), of which LRIM9 knockdown increases parasite load threefold (Vlachou et al 2005;Upton et al 2015). AGAP000151 (IRSP5), whose silencing increases both bacterial and parasite numbers (Dong et al 2006), and AGAP000570 (AgSGU), which is one of the most abundant peritrophic matrix proteins (Dinglasan et al 2009) and has important roles in ookinete attachment of Plasmodium falciparum (Mathias et al 2014), were also identified.…”
Section: Rapidly Evolving Sex-biased Genes Are Confined To a Few Biolmentioning
confidence: 99%
“…This obligatory blood-feeding requirement exposes female mosquitoes to a variety of microorganisms, and causes major transient changes in the mosquito gut microbiota. Not surprisingly, recent studies have led to renewed appreciation of the blood meal as a major immunostimulant for female mosquitoes (Bryant and Michel, 2014; Upton et al, 2015). Specifically, cellular immunity undergoes major shifts in the female mosquito after she blood feeds.…”
Section: Introductionmentioning
confidence: 99%